DETERMINANTE DE COMPOSIÇÃO DE CONSELHO DE ADMINISTRAÇÃO EM PEQUENAS E MÉDIAS EMPRESAS DE SOCIEDADE ANÔNIMA DE CAPITAL FECHADO DA REGIÃO DO ABC - Soares, Renato Ribeiro (2008)
The main objective of this study is to analyze the determinants of the composition the board of directors in small and medium private owned publicly traded companies in the region of ABC paulista. The study is motivated by the reason that in Brazil there is little or no studies approaching this subject and the studies presented abroad on analyzing the size board, the types of directories, the financial performance, the independence, etc., of the companies and none of them had its focus in composition the board of directors in small and medium private owned publicly traded companies. In the light of above, the current research is scheduled to try to find out an answer to the following questions: What factors were determinant to establish the composition of the board of directors in small medium private owned publicly traded companies of the region of ABC paulista? From this problem statement we established to the following hypotheses: If the power and the influence of CEO/Chairman of the board in companies of small and medium size is high, there will be possibilities to have external advisers; Should there be clear segregation of function between the CEO and the Chairman of the board and if the CEO would be interested to preserve his act and mandate then there will be a possibility to have internal advisers; Should there be interest in the efficiency, performance of the company, then there will be a possibility to have external advisers; Should the company be in the circle of expansion and maturity, then there will be a possibility to adopt and to have external advisers.(AU)